FOSFINA: RISCOS - FLORÃO, A.; FONSECA, R.V.; LOPES, M.; GABRIEL, M. M. (Visão Acadêmica, 2004)
A fosfina é amplamente utilizada para preservação de grãos armazenados em silos, sendo produzida no local da dedetização pela hidrólise dos fosfetos (fosfeto de alumínio, fosfeto de zinco, fosfeto de magnésio). Em conseqüência do número de óbitos registrados no IML - PR, nos últimos 2 anos por intoxicação com fosfina, pela ingestão proposital de pastilhas de fosfeto de alumínio, o presente trabalho foi desenvolvido com a finalidade de alertar sobre o uso indevido destas pastilhas. Neste artigo revemos os principais aspectos toxicológicos desta substância. PHOSPHINE: RISKS Abstract Phosphine is largely used for the preservation of stored grains in silos and it is produced in-situ through the hydrolysis of phosphides such as aluminum, zinc and magnesium phosphide. Phosphine is a gaseous substance that is extremely toxic to human beings and animals. As a result it is worth taking into consideration the number of phosphine-induced deaths that were registered during the last two years at the Institute for Legal Medicine, Paraná State. The present work was elaborated to draw attention at the misuse of aluminium phosphide pellets. Indeed, all the above reported phosphineinduced deaths were caused by the deliberate ingestion of aluminium phosphide. A review of the main toxicological aspects of phosphine is also presented.